(untitled) (Estudios sobre Educación, 2018)
The epistemology of tacit knowing in the ethics of mentoring is meant to be grounding for intelligent action. The structural and functional models delineated above provide a conceptual map for such action. The structure of tacit knowing consists of subsidiary awareness and focal awareness and the two poles of from-to knowing. Subsidiary awareness is on the internal (personal) pole, focal awareness is on the external (objective) pole. The function of tacit knowing has three aspects: selective, heuristic and persuasive, each having a conative and cognitive mode or trait. The driving force of this model is “intellectual passion” which in ethics is the judicial attitude, keeping the principle of justice in sight. Since the epistemology of tacit knowing presupposes free will, it must choose a duty bound ethics2. Specifically, the analysis of tacit knowing model presented here hones the awareness of the adult about his own processes of knowing, doing and persuasive acts, deliberately focusing on these processes and their grounding in free will. The adult’s understanding then serves his nurturing function, the training of the young to attain awareness of these same functions in him. The ethical aspect is the duty to pass on this knowledge to enable the child to become intelligently autonomous, to train him to develop the judicial attitude. Thus, both the morality of traits, that is being, and the morality of principles, that is doing, are fostered. However, the key is the fostering of the will to do right, that is fostering the “intellectual passion” grounded in the judicial attitude